Directly observed iron supplementation for control of iron deficiency anemia - Mohan Bairwa; Farhad Ahamed; Smita Sinha; Kapil Yadav; Shashi Kant; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2017)
Anemia is major public health problem affecting 1.6 billion people worldwide. The poor compliance of iron supplementation remains main contributor for high prevalence of anemia. The current paper reviewed the effectiveness of direct observation of oral iron supplementation on anemia. A systematic search was performed through electronic databases and local libraries. Search strategies used subject headings and key words "directly observed" and "iron supplementation." Searches were sought through April 2014. A total of 14 articles were included in the study. Findings were presented in three categories. First, all of those reported an improvement in compliance of iron supplementation. Second, reduction in the prevalence of anemia was reported by all and third, all except one reported increased blood hemoglobin level. Directly observed an iron supplementation is an effective approach for prevention and management of anemia in vulnerable groups. However, larger trials are needed before concluding that scaling up directly observed iron supplementation through community health volunteers would be beneficial.